Akhlak dalam Kehidupan Sosial Kemasyarakatan dan Bernegara: Kajian Literatur - Agung Nur Hidayat Hasyim; Ratih Amilia; Lailatul Muniroh; Mutaira Anisyah; Yuda Pratama; Aldi Anggara; Hafizul Husni (Journal of Research and Development on Public Policy, 2026)
Contemporary Indonesia faces the dual challenge of moral degradation at the societal level, characterized by increasing individualism and the decline of mutual cooperation (gotong royong), as well as a crisis of state ethics manifested in massive corruption and destructive identity politics. This article aims to explore the role of morality as a moral foundation that integrates social capital and good governance. This research uses a Literature Review method by searching literature from a reputable database, namely Google Scholar, for the period 2020-2026, which is analyzed using content analysis techniques. The results of the study indicate that morality functions as a fundamental variable that influences two domains simultaneously: strengthening social cohesion through the revitalization of the values of mutual cooperation and local wisdom, and increasing the integrity of governance through the internalization of the principles of accountability, transparency, and justice. These findings indicate that the reactualization of moral values originating from religion, Pancasila, and local wisdom is an absolute prerequisite for building a civil society and government with integrity. It is recommended that there be a comprehensive strategy through character education, cultural bureaucratic reform, and consistent law enforcement to overcome the social and state ethics crisis holistically.